Prognostic factors for corneal graft recovery after severe corneal graft rejection following penetrating keratoplasty - Yamazoe, Katsuya (BioMed Central, 2013)
BACKGROUND: To investigate the outcome and prognostic factors for corneal graft recovery after severe corneal graft rejection following penetrating keratoplasty (PKP) treated with topical and systemic steroids. METHODS: Fifty-eight eyes in 58 patients with severe corneal graft rejection following PKP were treated with topical and systemic steroids. Factors affecting the reversibility and maintenance of graft transparency were analyzed. RESULTS: Graft transparency was restored in 37 of 58 eyes (63.8%). Clarity of the graft was maintained in 25 of 37 eyes after transparency was restored, while corneal decompensation developed at a mean of 6.0 ± 4.3 months in the remainder. The interval between rejection and treatment with systemic steroids was shorter in cases that recovered graft transparency (OR, 0.88, 95% CI. 0.80–0.97, P = 0.0093). Corneal decompensation after the recovery of corneal transparency tend to occur in cases of regraft (OR, 0.09, 95% CI. 0.01–0.54, P = 0.0091). CONCLUSIONS: Severe corneal graft rejection after PKP was reversible in approximately two-thirds of the cases, with graft transparency being maintained in two-thirds of them when treated with both topical and systemic steroids. Early treatment confers a benefit in terms of the recovery of graft transparency.